2017
DOI: 10.3389/fcimb.2017.00516
|View full text |Cite
|
Sign up to set email alerts
|

Oral Microbiota: Microbial Biomarkers of Metabolic Syndrome Independent of Host Genetic Factors

Abstract: The oral microbiota plays a critical role in both local and systemic inflammation. Metabolic syndrome (MetS) is characterized by low-grade inflammation, and many studies have been conducted on the gut microbiota from stool specimens. However, the etiological role of the oral microbiota in the development of MetS is unclear. In this study, we analyzed the oral and gut microbiome from 228 subgingival plaque and fecal samples from a Korean twin-family cohort with and without MetS. Significant differences in micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
42
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 60 publications
7
42
0
1
Order By: Relevance
“…Alternatively, as our urbanization gradient mostly represents changes in terms of diet and habitat, but not medication, is is tempting to propose that the loss of both bacterial and eukaryotic diversity in highly industrialized and urban environments is mostly due to changes in medical practices, such as antibiotics use. Finally, we did observe a decline in abundance-weighted phylogenetic diversity ( 2 D ph ), which is more sensitive to subtle changes in environmental conditions than richness measures 38 . This small but significant decrease might represent an early response to urbanization-related changes in lifestyle, for example due to changes in diet.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Alternatively, as our urbanization gradient mostly represents changes in terms of diet and habitat, but not medication, is is tempting to propose that the loss of both bacterial and eukaryotic diversity in highly industrialized and urban environments is mostly due to changes in medical practices, such as antibiotics use. Finally, we did observe a decline in abundance-weighted phylogenetic diversity ( 2 D ph ), which is more sensitive to subtle changes in environmental conditions than richness measures 38 . This small but significant decrease might represent an early response to urbanization-related changes in lifestyle, for example due to changes in diet.…”
Section: Discussionmentioning
confidence: 71%
“…Cross denotes mean. and saliva microbiome seems to be related to health in opposing ways 11,38 . Still, this positive correlation could be related to the degree to which individuals are exposed to environmental bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 4 indicates that during the treatment timeline, strictly anaerobic short-chain fatty acid-producing gut bacteria typically beneficial for health, such as Faecalibacterium, Anaerostipes, Blautia, and Roseburia (De Vos and de Vos, 2012; Rajilic-Stojanovic and de Vos, 2014; Reichardt et al, 2018), decreased significantly at T2. In contrast, pathobionts or members of oral microbiota such as Enterococcus, Eggerthella, Peptococcus, and Rothia (Weber and Gold, 2003;Zaura et al, 2009;Yeh et al, 2016;Si et al, 2017;Ugarte-Torres et al, 2018), showed a substantial increase at T2. Interestingly, the tendency to increase in T2 was also observed for the obligate anaerobic gut microbes, such as Akkermansia, Bifidobacterium, and Methanobrevibacter, which are known to be the most stable in gut microbiota under external perturbations and assumed dependent on host genetic makeup (Goodrich et al, 2016) (Supplementary Material 6).…”
Section: Associations Between Bacterial Taxa and Patient Characteristicsmentioning
confidence: 97%
“…A small number of studies have used network analysis or genome scale modeling to study the oral microbiome. Network analysis was used to analyze the co-occurence mechanisms among oral microbes and gut microbes [114]. It was found that Neisseria elongata and Granulicatella adiacens were involved in causing metabolic syndrome (MetS).…”
Section: Modeling Methodologiesmentioning
confidence: 99%